1991
DOI: 10.1007/bf00142675
|View full text |Cite
|
Sign up to set email alerts
|

Dark-adapted luminance-response functions with skin and corneal electrodes

Abstract: Normative dark-adapted electroretinograms were recorded simultaneously with a skin electrode and corneal electrode for varying stimulus intensities. The electroretinogram b-wave amplitudes for each electrode were fitted by the Naka-Rushton equation, and the parameters Vmax, K and n were evaluated. A comparison of parameters between the two electrodes showed a significant difference for Vmax and K but not for n. Vmax was approximately eight times smaller and K was 0.3 log unit smaller for the skin electrode tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
5
12
0
Order By: Relevance
“…In our results, Vmax was significantly less variable than K in terms of intersubject CoV and also, in some cases, for inter-ocular and inter-session LoA. Wali and Leguire also found K to be the most variable parameter for the intensity-response series of the scotopic b-wave [43]. In a previous paper, we reported the variability of PhNR amplitudes measured in different ways in response to a stimulus of intensity 1.76 log phot td.s [21].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In our results, Vmax was significantly less variable than K in terms of intersubject CoV and also, in some cases, for inter-ocular and inter-session LoA. Wali and Leguire also found K to be the most variable parameter for the intensity-response series of the scotopic b-wave [43]. In a previous paper, we reported the variability of PhNR amplitudes measured in different ways in response to a stimulus of intensity 1.76 log phot td.s [21].…”
Section: Discussionsupporting
confidence: 64%
“…Bradshaw et al, (2004) also found that, when scaled for amplitude, the b-wave intensity-response series of the skin and corneal electrodes were similar [47]. In contrast, Wali and Leguire (1991) found skin electrode responses to have a lower K value than corneal electrode responses [43], indicating a greater sensitivity of the responses recorded using the skin electrode. However they were analysing scotopic b-wave amplitudes, rather than photopic ERGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dark-adapted ERG amplitudes over a range of stimulus intensities constitute the luminance-response (L-R) function, which can be fitted by the Naka-Rushton equation [1]: V= (Vmax In)/(I n + Kn), with the use of nonlinear [2][3][4][5] or linear [6][7] regression. V is the measured b-wave amplitude at luminance I, Vmax is the maximum b-wave amplitude obtained, K is the half saturation constant (i.e., the luminance at which V = 89 Vmax) and n is a dimensionless constant that represents the slope of the function.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with skin electrodes have demonstrated that peak-to-peak amplitude can show variability as the skin electrode can move during the exam, reducing the amplitudes on the final steps as the electrodes lose adherence to the skin (11) . However, comparative studies demonstrated that the variability found with skin electrodes is similar to the variability found with corneal contact electrodes, and examiners need to ensure that the electrode is correctly placed close to the lower orbital rim during the entire exam (9,22) . The ISCEV protocol and the recommendation for each laboratory to determine its own normative values are extremely important for a high quality test.…”
Section: Discussionmentioning
confidence: 99%